2012
DOI: 10.7314/apjcp.2012.13.7.3373
|View full text |Cite
|
Sign up to set email alerts
|

Head and Neck Squamous Cell Carcinoma in Iranian Patients and Risk Factors in Young Adults: a Fifteen-Year Study

Abstract: Background: Head and neck squamous cell carcinoma (HNSCC) is the 8th most common cancer worldwide. Although older age, male gender, smoking and alcohol consumption are known risk factors, an increasing number of HNSCC patients are without typical risk factors. Our aim was to define demographics of HNSCC in Iran and the potential risk factors related to Iranian ethnicity and lifestyle. Methods: We conducted a crosssectional analytical study on 262 patients with primary SCC of the larynx, hypopharynx or tongue r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(19 citation statements)
references
References 45 publications
2
14
1
Order By: Relevance
“…(15) Mirzaei et al and Mafi et al reported that the thyroid and larynx cancers were the most prevalent head and neck malignancies, which confirmed our results. (16,17) Additionally, our results showed that head and neck cancer patients were usually in the eighth (25%) and seventh (21%) decades of life. Shahsavari et al also studied head and neck cancer patients in Tehran, Iran, and arrived at the same conclusion that the eighth (27%) and seventh (22%) decades of life were the most common decades for the development of head and neck cancer.…”
Section: Discussionsupporting
confidence: 50%
“…(15) Mirzaei et al and Mafi et al reported that the thyroid and larynx cancers were the most prevalent head and neck malignancies, which confirmed our results. (16,17) Additionally, our results showed that head and neck cancer patients were usually in the eighth (25%) and seventh (21%) decades of life. Shahsavari et al also studied head and neck cancer patients in Tehran, Iran, and arrived at the same conclusion that the eighth (27%) and seventh (22%) decades of life were the most common decades for the development of head and neck cancer.…”
Section: Discussionsupporting
confidence: 50%
“…(Elango et al, 2006) Earlier reports have shown that tongue cancer has increased among the non-tobacco users, suggesting a review of the clinico-epidemiological factors and molecular changes in OTSCCs. (Mafi et al, 2012;Arvind Krishnamurthy et al, 2013;Bektas-Kayhan et al, 2014) Human Papillomavirus (HPV), an epitheliotropic DNA virus, is known to be an etiologic agent in the tumorigenesis of cervical cancers. However, unlike cervical cancer, oral cancers are not widely accepted as a completely HPV associated malignancy.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the most common site of involvement was the skin of the head and neck in the southeast of Iran (9). In most articles, skin cancers are not considered in the category of head and neck cancers, so the larynx was reported as the most common site of involvement in Kerman (46.76%) (10); in the same vein, Mafi et al reported laryngeal cancer as the most common type of head and neck cancers in both sexes in Iran (11). In the present study, the second most common site of involvement was thyroid after skin, probably due to the referral of laryngeal cancer to another medical center.…”
Section: Discussionmentioning
confidence: 99%